The evolution of pedipalps and glandular hairs as predatory devices in harvestmen (Arachnida, Opiliones) - Wolff, J.; Schönhofer, A.; Martens, J.; Wijnhoven, H.; Taylor, Christopher; Gorb, S. (Wiley-Blackwell Publishing, 2016)
Pedipalps are the most versatile appendages of arachnids. They can be equipped with spines (Amblypygi), chelae (Scorpiones), or adhesive pads (Solifugae), all of which are modifications to grasp and handle fast-moving prey. Harvestmen (Opiliones) show a high diversity of pedipalpal morphologies. Some are obviously related to prey capture, like the enlargement and heavy spination of Laniatores pedipalps. Many Dyspnoi, by contrast, exhibit thin, thread-like pedipalps that are covered with complex glandular setae (clavate setae). These extrude viscoelastic glue that is used to immobilize prey items. Comparable setae (plumose setae) have previously been found in representatives of both Eupnoi and Dyspnoi, yet comprehensive data on their distribution are lacking. This study examined the distribution and ultrastructure of glandular setae in harvestmen and related them to pedipalpal morphology. Pedipalpal and setal characters were analysed in a phylogenetic framework. We found that glandular setae are synapomorphic for and widespread in the Palpatores clade (Eupnoi plus Dyspnoi). Their occurrence correlates with pedipalp morphology and feeding habit. Remnants of arthropod cuticular structures or secretions, frequently found attached to glandular setae, and behavioural observations, underlined the importance of the setae for capturing and securing prey.We hypothesize that glandular setae evolved as an adaptation to capture small and agile prey, which are hard to catch with a capture basket. Details of ultrastructure indicate that the setae are derived sensilla chaetica, with both a secretory and sensory function. Derived ultrastructural characters of the glandular setae, such as slit-like channel openings and a globular arrangement of the microtrichia, may increase their effectiveness. The functional role of further pedipalpal modifications, such as apophyses, stalked and hyperbendable joints, and curved segments, as well as sexual dimorphism and ontogenetic polymorphism, are discussed. Some implications of the results obtained for the taxonomic treatment of Phalangiidae are also discussed. These results shed new light on the biology and evolutionary history of this fascinating group of arthropods.